Strongly localized modes in discrete salerno model - Umarov, Bakhram; Benseghir, A; Wan Abdullah, Wan Ahmad Tajuddin; C., H. Ooi; Bouketir, Ahmed; Messikh, Azeddin (IDOSI Publication, 2013)
This paper is devoted to the investigation of the existence and stability of strongly localized modes in discrete media in Salerno model by using linear analysis method. The regions of stability and instability are determined. Also the existence of localized modes for different values of parameters is shown numerically by homoclinic orbits intersection method.